High rate of unintended pregnancy among pregnant women in a maternity hospital in Córdoba, Argentina: a pilot study - Schenk Verónica; Bahamondes M; Palena Celina; Bahamondes Luis; Fernandez-Funes Julio (BMC, 2009)
Abstract Background Although Argentina has a new law on Reproductive Health, many barriers continue to exist regarding provision of contraceptive methods at public healthcare facilities. Methods We asked 212 pregnant women selected at random at the Maternity and Neonatal Hospital, Córdoba, Argentina, to participate in our descriptive study. Women were asked to complete a structured questionnaire. The objectives were to determine the rate of unintended pregnancies, reasons for not using contraception, past history of contraceptive use, and intended future use. Results Two hundred women responded to the questionnaire. Forty percent of the women stated that they had never used contraception and pregnancy was declared unintended by 65%. In the unintended pregnancy group, almost 50% of women said that they had not been using a contraceptive method because they were "unaware about contraception", and 25% stated that their contraceptive method had failed. Almost 85% of women stated that they intended to use contraception after delivery. Conclusion Approximately two-thirds of all pregnancies in this sample were unintended. Although the data is limited by the small sample size, our findings suggest that our government needs to invest in counseling and in improving the availability and access to contraceptive methods.